Acute Schistosomiasis in European Students Returning From Fieldwork at Lake Tanganyika, Tanzania. Issue 6 (22nd September 2013) - Steiner, Florian; Ignatius, Ralf; Friedrich‐Jaenicke, Barbara; Dieckmann, Sebastian; Harms, Gundel; Poppert, Sven; Mockenhaupt, Frank P.
Abstract: Background: Schistosomiasis is common in many African regions and poses a risk for travelers and the local population. So far, schistosomiasis in travelers or expatriates returning from the Tanzanian bank of Lake Tanganyika has not been reported. Methods: We report a group of students who sought treatment with signs of acute schistosomiasis after having returned from Lake Tanganyika, Tanzania. Information as to travel and exposure as well as clinical and laboratory data were collected. Results: Schistosomiasis was diagnosed in 8 of 16 students from Berlin, Germany, who had returned from a 2‐ to 3‐month stay of fieldwork in Kigoma District at Lake Tanganyika, Tanzania. All 16 students reported frequent freshwater exposure at the lake. Six patients showed signs of acute schistosomiasis and had fever, and some of them also had cough, weakness, headache, or abdominal pain. Eosinophilia was present in five of the six symptomatic individuals. Notably, two serologically enzyme‐linked immunosorbent assay (ELISA)‐positive individuals did not report or present with symptoms or abnormal laboratory parameters. Schistosoma mansoni eggs were found in one symptomatic and one asymptomatic individual each. Blood and stool samples from the other eight individuals who were equally exposed to freshwater yielded negative results. Conclusions: This is the first report of an outbreak of acute schistosomiasis imported from the Tanzanian shore of Lake Tanganyika and highlights the risk for travelers and the local population of acquiring the infection in that part of Tanzania. It provides arguments for routine serological screening for schistosomiasis in individuals who had prior freshwater contact in endemic areas, irrespective of symptoms or other laboratory findings.